The Cambridge companion to Christian ethics - Gill, Robin (Cambridge, UK ; New York : Cambridge University Press, 2012)
"In this second edition of the best-selling Cambridge Companion to Christian Ethics, Robin Gill brings together twenty essays by leading experts, to provide a comprehensive introduction to Christian ethics which is both authoritative and up to date. This volume boasts four entirely new chapters, while previous chapters and all bibliographies have been updated to reflect significant developments in the field over the last decade. Gill offers a superb overview of the subject, examining the scriptural bases of ethics as well as discussing Christian ethics in the context of contemporary issues, including war and the arms trade, social justice, ecology, economics, medicine and genetics. All of the contributors have a proven track record of balanced, comprehensive and comprehensible writing making this book an accessible and invaluable source not only for students in upper-level undergraduate courses, graduate students and teachers, but anyone interested in Christian ethics today"--
"In this second edition of the best-selling Cambridge Companion to Christian Ethics, Robin Gill brings together twenty essays by leading experts, to provide a comprehensive introduction to Christian ethics which is both authoritative and up to date. This volume boasts four entirely new chapters, while previous chapters and all bibliographies have been updated to reflect significant developments in the field over the last decade. Gill offers a superb overview of the subject, examining the scriptural bases of ethics as well as discussing Christian ethics in the context of contemporary issues, including war and the arms trade, social justice, ecology, economics, medicine and genetics. All of the contributors have a proven track record of balanced, comprehensive and comprehensible writing making this book an accessible and invaluable source not only for students in upper-level undergraduate courses, graduate students and teachers, but anyone interested in Christian ethics today"--
Machine generated contents note: Part I. The Grounds of Christian Ethics: 1. Making moral decisions Rowan Williams; 2. Moral traditions in eastern and western Christianity Robin W. Lovin; 3. The Old Testament and Christian ethics John Rogerson; 4. The Gospels and Christian ethics Allen Verhey; 5. The epistles and Christian ethics Stephen C. Barton; Part II. Approaches to Christian Ethics: 6. Natural law and Christian ethics Stephen J. Pope; 7.
Includes bibliographical references and index
Keywords: Christian ethics